2005
DOI: 10.1159/000085435
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Eczema at One Month of Age Is Associated with Cord Blood Eosinophilia and Subsequent Development of Atopic Dermatitis and Wheezing Illness until Two Years of Age

Abstract: Background: Physiological and pathological skin eruptions are commonly encountered in neonates in our clinical practice. However, the types of skin eruptions that are associated with the subsequent development of atopic dermatitis and the mechanisms of these associations remain uncertain. Methods: A total of 105 newborn babies with normal delivery were enrolled in this prospective cohort study. The cord blood eosinophil count was measured and the neonates were examined at 1 month of age and followed until 8 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 50 publications
2
6
1
Order By: Relevance
“…In this study, the IgE and eosinophil counts in umbilical cord blood did not differ significantly between neonates who developed AD and those who did not, the result differing from those reported previously by Ferguson et al [2] and Matsumoto et al [3], respectively. These discrepancies might be explained by the differences in the follow‐up periods, numbers of subjects and measurement methods used among the studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this study, the IgE and eosinophil counts in umbilical cord blood did not differ significantly between neonates who developed AD and those who did not, the result differing from those reported previously by Ferguson et al [2] and Matsumoto et al [3], respectively. These discrepancies might be explained by the differences in the follow‐up periods, numbers of subjects and measurement methods used among the studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Although several interesting theories, e.g. cord blood IgE [2], cord blood eosinophil counts [3], maternal IgE in the placenta [4], macrophage‐derived chemokine (MDC; CCL22) [5, 6], infantile eosinophil counts [7], maternal IFN‐γ/IL‐4 ratios [8], eotaxin [9] and regulatory T cells [10], have been proposed, the precise mechanisms still remain under debate.…”
Section: Introductionmentioning
confidence: 99%
“…In the analysed LINA subcohort, CC was the most prevalent skin manifestation within the first year of life (57%), followed by AD (13‐15%) which is comparable with previous cohort studies of dermal outcomes in early infancy (CC: 35.7‐56.3% , AD: 8‐10% ). Although, there is no clear association between cradle cap and atopic dermatitis, it has been reported that a certain number of neonates with cradle cap develop an atopic dermatitis . Possible links from the present analyses which could point out the possibility of an atopic component in cradle cap are mentioned later in the discussion.…”
Section: Discussionmentioning
confidence: 48%
“…In an ethnically mixed South African cohort with diverse genetic and environmental background, cord blood eosinophils were not predictive of the development of atopic disease (asthma, AD, food allergy, allergen‐induced urticaria) until 1 year of life . In a Japanese cohort study, cord blood eosinophilia was significantly associated with infantile eczema at 1 month of life; latter was associated with AD and recurrent wheezing until 2 years of life . Calbi consistently reported that blood eosinophilia at the third day of life was predictive of atopy (AD, recurrent wheezing, allergen‐induced urticaria) until 3 years of life in 41–54% in a mixed atopic/non‐atopic as well as in an atopic cohort .…”
Section: Discussionmentioning
confidence: 99%